2015
DOI: 10.3389/fcell.2015.00060
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine transfer from cerebrospinal fluid into choroid plexus and brain is affected by brefeldin A, low sodium, BCH, and phloretin, in ventriculo-cisternal perfused rabbits

Abstract: Background: Thyroxine (T4) hormone is synthesized by the thyroid gland and then released into the systemic circulation where it binds to a number of proteins. Dysfunction in T4 transport mechanisms has been demonstrated in multiple central nervous system (CNS) diseases including Alzheimer's disease. In the presence of different compounds that inhibit potential T4 transport mechanisms, this study investigated the transfer of T4 from cerebrospinal fluid (CSF) into Choroid Plexus (CP) and other brain tissues. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The steady-state extraction of 125 I-T 4 at the blood side (basolateral) of the perfused CP over 1 h was calculated relative to the extracellular marker 14 C-mannitol. This allows to measure the extraction of 125 I-T 4 in presence of drugs known to inhibit the efflux transporters, at the basolateral side of the CP, such as probenecid, verapamil, BCH, and indomethacin ( 24 , 25 ). The net extraction of 125 I-T 4 from the blood to CP, which represents the non-specific paracellular loss of T 4 , was calculated by subtracting the extraction of 14 C-mannitol from that of 125 I-T 4 (Ex.…”
Section: Resultsmentioning
confidence: 99%
“…The steady-state extraction of 125 I-T 4 at the blood side (basolateral) of the perfused CP over 1 h was calculated relative to the extracellular marker 14 C-mannitol. This allows to measure the extraction of 125 I-T 4 in presence of drugs known to inhibit the efflux transporters, at the basolateral side of the CP, such as probenecid, verapamil, BCH, and indomethacin ( 24 , 25 ). The net extraction of 125 I-T 4 from the blood to CP, which represents the non-specific paracellular loss of T 4 , was calculated by subtracting the extraction of 14 C-mannitol from that of 125 I-T 4 (Ex.…”
Section: Resultsmentioning
confidence: 99%
“…The increased accumulation of T 4 in the CP by TTR may be due to reduced basolateral efflux (from choroid epithelial cells to plasma) as well as an augmented uptake of T 4 from CSF. The T 4 efflux from the CSF involves a number of transporters and is saturable in presence of unlabelled T 4 . Despite the important role of TTR in TH homeostasis, mice lacking the TTR gene maintain normal functioning of thyroid glands in the face of significant reduction in total serum T 4 concentration .…”
Section: Discussionmentioning
confidence: 99%
“…The increased accumulation of T 4 in the CP by TTR may be due to reduced basolateral efflux (from choroid epithelial cells to plasma) as well as an augmented uptake of T 4 from CSF. The T 4 efflux from the CSF involves a number of transporters 29 and is saturable in presence of unlabelled Using the same model it was found that TTR was not essential for TH to reach the brain. 8 This is not surprising given there are numerous mechanisms for T 4 transport, and a number of TBG may take over the role of TTR in TTR-null mice.…”
Section: Effects Of Ttr On 125 I-t 4 / 125 I-aβ40 In the Brainmentioning
confidence: 98%